How the Vertebrate Brain Regulates Behavior : direct from the lab - Donald W Pfaff (Harvard University Press, 2017)
Historically, neuroscientists often chose to work with the simplest non-mammalian species out of a fear that the mammalian brain would be too complex and would defy precise methodology. My lab's work has proven that by choosing problems and methods with care, it is possible to explain a mammalian behavior. The timing of this book reflects that it is now fifty years since I discovered hormone receptors in the brain. These hormone receptors led us to unravel the neural circuitry for a laboratory animal mating behavior and also permit us to use molecular biological techniques in the brain. The behavior explained is a social behavior, which makes it still more surprising that it has been susceptible of analysis. My lab's accomplishments typify, in one scientific story, what needs to happen as neuroscientists continue to explore mechanisms in the mammalian brain.